Bottleneck for reactive molar mass in the polymerization of propylene oxide initiated with potassium t-butoxide - Yang, Pengfei; Zhu, Xuwei; Yu, Yanhong; Xia, Yong mei; Li, Tianduo (Journal of applied polymer science, 2009)
The anionic polymerization of propylene oxide was investigated with potassium t-butoxide as an initiator, and the solvent hexamethyl phosphoric triamide was used in controlling experiments. The relative molar mass limit of the products was determined as about 2700, and the C==C double bond was found to exist by NMR. In situ Fourier transform infrared spectroscopy was used to monitor the whole polymerization process until the absorbance reached a constant value and the system reached equilibrium. However, propylene oxide still existed in the system, and alkoxide was detected in the reaction system by ²³Na-NMR. On the basis of these results, we deduced that the residual alkoxide was not active enough to initiate propylene oxide polymerization in the near end of the polymerization. Therefore, there might have been another factor that limited the increase of the relative molar mass of poly(propylene oxide) in addition to chain transfer.